Colorimetric detection of SARS-CoV-2 by uracil-DNA glycosylase (UDG) reverse transcription loop-mediated isothermal amplification (RT-LAMP). (July 2022) - Lai, Meng Yee; Bukhari, Fatma Diyana Mohd; Zulkefli, Nur Zulaikha; Ismail, Ilyiana; Mustapa, Nur Izati; Soh, Tuan Suhaila Tuan; Hassan, Afifah Haji; Peariasamy, Kalaiarasu M; Lee, Yee Leng; Suppiah, Jeyanthi; Thayan, Ravindran; Lau, Yee Ling
Highlights: RNA-purification–free method was developed for the detection of SARS-CoV-2 One-step uracil-DNA glycosylase reverse transcription loop-mediated isothermal amplification was used to detect SARS-CoV-2 Result were obtained by direct observation of end products by the naked eye ABSTRACT: Objectives: Preventing reverse transcription loop-mediated isothermal amplification (RT-LAMP) carryover contamination could be solved by adding deoxyuridine triphosphate (dUTP) and uracil-DNA glycosylase (UDG) into the reaction master mix. Methods: RNA was extracted from nasopharyngeal swab samples by a simple RNA extraction method. Results: Testing of 77 samples demonstrated 91.2% sensitivity (95% confidence interval [CI]: 78–98.2%) and 100% specificity (95% confidence interval: 92–100%) using UDG RT-LAMP. Conclusion: This colorimetric UDG RT-LAMP is a simple-to-use, fast, and easy-to-interpret method, which could serve as an alternative for diagnosis of SARS-CoV-2 infection, especially in remote hospitals and laboratories with under-equipped medical facilities.